Translational control of the AZFa gene DDX3Y by 5′UTR exon-T extension - Jaroszyński, Łukasz; Zimmer, Jutta; Fietz, D.; Bergmann, M.; Kliesch, S.; Vogt, Peter H. (International journal of andrology, 2011)
The human DEAD-box Y (DBY) RNA helicase (aka DDX3Y) gene is thought to be the major azoospermia factor a (AZFa) gene in proximal Yq11. Although it is transcribed in many tissues, the protein is expressed only in spermatogonia. In this study, we demonstrate that this translational control mechanism is probably germ cell-specific because of its association with expression of a distinct class of DDX3Y testis transcripts present only in pre- and post-meiotic male germ cells. They are initiated from a second distal DDX3Y promoter domain at two distinct start sites in the gene’s 5′ untranslated region (UTR) exon-T sequence. With the aid of an EGFP-3xFLAG reporter cassette cloned downstream of DDX3Y minigenes containing exons 1-4 and two different exon-T extensions, we discovered that DDX3Y translation is influenced by the presence of several ATG triplets located in exon-T, thus upstream of the main translational ATG start codon in exon 1. Strong translational repression of the DDX3Y minigene transcripts was observed when they contained the longest exon-T sequence with five upstream ATG triplets (uATGs). The potential formation of complex distinct stem-loop structures serve here as additional repressor element. Only minor translational attenuation was seen for the DDX3Y minigene transcripts when containing the shortest exon-T sequence, that is, starting at first transcriptional start site (coined ‘T-TSS-I’). It was completely released after its single uATG was abolished by mutation. As we found DDX3Y transcripts with the longest exon-T sequence predominantly in spermatids, our results suggest that the amount of DDX3Y protein in pre-meiotic germ cells and its absence in post-meiotic germ cells are tightly controlled by the different extensions of exon-T in this germ cell-specific DDX3Y transcript class.
Gesehen am 31.07.2019